2017
DOI: 10.1037/stl0000090
|View full text |Cite
|
Sign up to set email alerts
|

Active reading questions as a strategy to support college students’ textbook reading.

Abstract: This pilot study and experiment investigates the use of active reading questions (ARQs) as a potential reading tool to support college students’ textbook reading. The pilot study compares the self-selected use of ARQs and PowerPoint slides (PPTs) in 4 college classrooms and indicated that both reading strategies had similar but limited effects on learning. In the experiment, a reading tool (e.g., ARQs or PPTs) was required or participants were given no tool at all (control group). Time spent reading and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Written recall depicts a thorough picture of comprehension, primarily because it has no retrieval cues or tester interference (Bernhardt, 2011). Written recall invokes deeper-level processing than information recognition that is tested via multiple-choice (Fleck et al, 2017). It taps into the encoding of individual propositions (Irwin & Mitchell, 1983), the discerning of essential and nonessential content, and the integration of multiple pieces of information into a coherent mental representation (Martin et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Written recall depicts a thorough picture of comprehension, primarily because it has no retrieval cues or tester interference (Bernhardt, 2011). Written recall invokes deeper-level processing than information recognition that is tested via multiple-choice (Fleck et al, 2017). It taps into the encoding of individual propositions (Irwin & Mitchell, 1983), the discerning of essential and nonessential content, and the integration of multiple pieces of information into a coherent mental representation (Martin et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One type of adjunct question is the targeted segment (TS) question, also referred to as “what question.” TS question asks about specific text content and can be answered by information solely presented in the text. Research has shown that TS questions enhance text memory and comprehension for L1 readers (Butler, 2010; Carroll et al, 2007; Fleck et al, 2017; Hamilton, 1985; Healy et al, 2017; Kapp et al, 2015; Walczyk & Hall, 1989; Weinstein et al, 2016; Zhou et al, 2015), particularly when the questions overlap with those in final assessment (Hamaker, 1986; McDaniel et al, 2012). Less‐skilled readers especially benefit from adjunct questions (Callender & McDaniel, 2007; Peverly & Wood, 2001), whereas proficient readers perform well with or without adjunct questions (Stiegler‐Balfour & Benassi, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…SoTL is defined as the "systematic study of teaching and/or learning and the public sharing and review of such work through presentations, performance, or publications" (McKinney, 2007, p. 39). For example, Fleck, Richmond, Rauer, Beckman, and Lee (2017) developed a method of active reading to increase students' learning and students' use and efficiency of reading textbooks in their classes and found that compared to the use of Power-Point presentations, that students who engage in active reading were more motivated to engage in course work and academically do better. Richmond, Gurung, and Boysen (2016) suggested that SoTL research is ripe for growth, especially at the graduate student level.…”
Section: Oh the Research That Students Need To Do In Graduate School!mentioning
confidence: 99%
“…It is hard to test student preclass reading directly since self-report can be unreliable, particularly when students know that their report may influence their grade (Sappington et al, 2002). However, researchers have tested various interventions to evaluate their effectiveness at increasing student performance on assessments (e.g., Maurer & Longfield, 2015) or compliance rates on anonymous self-report measures (e.g., Fleck et al, 2017; Hoeft, 2012). Some of these approaches have involved voluntary interventions.…”
Section: Student Reading Practicesmentioning
confidence: 99%